Concrete pavements as a source of heating and cooling - Keikha, P.; Hall, M.R.; Dawson, Andrew (2010)
There is great potential to use the large open space of pavement structures, equipped with an embedded pipe network, in conjunction with a heat pump, to provide heating and cooling for adjacent buildings, e.g. airport terminals, shopping centres etc, here termed a Pavement Source Heat Pump (PSHP). Due to the high thermal mass of pavement materials, seasonal temperature fluctuation under the pavement is much less than the temperature fluctuation of ambient air. Therefore, pavements can be utilised as a low grade heat source during winter and as a heat sink during summer. Airports, for example, provide a key potential application as they are very large consumers of energy, typically have very high cooling demands, have a large amount of adjacent pavement area, and are of a similar arrangement throughout the world. In this paper, the temperature distribution into pavements with different thermo-physical properties was modelled in order to evaluate their effects on depth of seasonal temperature fluctuation. The results show that there is a linear relationship between the thermal diffusivity and depth of seasonal temperature fluctuation and it decreases in relation to the thermal diffusivity of the pavement.